Efficient matching of services with users in opportunistic network environments. (2015) - Smith, Anthony; Berry, Stuart; Hill, Richard
Opportunistic networks are a specific type of wireless ad hoc network where there is an absence of a continuous end-to-end path. The proliferation of mobile devices with Wi-Fi capability creates opportunities to forward packets by utilising nodes as they present themselves. Such a dynamic networking environment enables services to be advertised by propagating from device to device, in order that all users in an area receive them. However, excessive propagation of service advertisements consumes energy from mobile devices, whilst also degrading the users' experience if they receive adverts for services that are misaligned with their personal interests. In this article, we propose an architecture for a protocol and an algorithm that facilitates the matching of relevant service adverts with interested recipients in an opportunistic networking environment, whilst serving to minimise energy consumption.